How hours of work affect occupational earnings. - Hecker, Daniel (Monthly Labor Review, 1998)
A discussion of the way in which hours of work impact on occupational earnings. Data are drawn from the 1997 Current Population Survey, the monthly household survey that provides the fundamental measurements of the American labor force and employment. In most managerial, management-related, production, sales, and transportation occupations, it was found that workers with longer hours earn at a higher hourly rate. However, the reverse was the case for certain occupations, including engineers, computer specialists, schoolteachers, and building workers, where extra hours may yield job satisfaction but not much more money.